Studi Kelayakan Bisnis Perusahaan Provillo Shoes - Laili, Silvia Nur (Maliki Interdisciplinary Journal, 2025)
The footwear industry in Indonesia continues to grow alongside increasing public awareness of high-quality local products. Provillo Shoes, as one of the key players in this industry, demonstrates significant potential in meeting market demand through product innovation, digital marketing strategies, and a commitment to environmental sustainability. With an initial investment of IDR 500 million, the company is capable of producing up to 1,000 pairs of shoes per day. This study evaluates the business feasibility through analyses of legal, environmental, market, managerial, and financial aspects. The findings reveal that Provillo Shoes is viable for development, with high profit potential supported by solid financial ratios such as a Payback Period of 10 months and an IRR of 15%. However, challenges such as production waste and intense competition from global brands require attention. Innovative strategies in production, marketing, and environmental management are essential to ensure the sustainability of this business.